(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This scientific article discusses the analysis and research of the problem, requirements, as well as the main factors influencing to improve their ecological infrastructure of modern cities. As an example, the ecological situation in Tashkent, the capital of Uzbekistan, was studied. Based on the analysis, conclusions and recommendations for organizing and improving the ecological infrastructure of cities were developed.